Upaya Peningkatan Program Keagamaan Melalui Kegiatan Perayaan 1 Muharram Dan Pelestarian MDA Al-Abror Di Desa Aek Godang: Peran Mahasiswa KKN 01 Stain Madina 2023 - Suci Permadani Hasibuan; Annisa Siregar; Nisbahus Salamah; Yuli Astiani Siregar; Padlan Hamidi Matondang; AHD. Fauzi; Muhammad Faujan; Artha Maulida Nst; Mahrani Aziz (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Real work education (KKN) is a service to the community carried out by students through the guidance of lecturers. This service aims to establish synergy between universities and the community, especially for students to apply the knowledge gained from higher education. In welcoming the month of Muharram, the people of Aek Godang have never celebrated 1 Muharram and also the MDA School in Aek Godang Village experienced obstacles because one of the facilities was that students did not meet the capacity they should have to carry out learning at the MDA. This research aims to practice 1 Muharram and also preserve MDA which is no longer operating. The results of this research reveal that: 1. The practice of Muharram 1 in Aek Godang village, Hulu Sihapas sub-district, North Padang Lawas Regency, namely the implementation of recitations by inviting teachers to deliver tausiyah regarding the Islamic New Year.2. Conservation of MDA Al ABROR Aek Godang Village, Hulu Sihapas District, North Padang Lawas Regency, namely socializing to children that studying religion is just as important as gaining general knowledge and also telling children that studying religion is an important thing because it is guides and also guidelines for the life of Muslims.